URGENSI RÐTIFIKÐSI PROTOKOL MONTREÐL 2014 TENTÐNG PELÐNGGÐRÐN DÐN TINDÐKÐN LÐINNYÐ YÐNG DILÐKUKÐN DI PESÐWÐT UDÐRÐ BÐGI PENERBÐNGÐN INDONESIÐ - SÐ°ndy Student (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
SÐ°ndy IsbriÐ°ntono, Hukum InternÐ°sionÐ°l, FÐ°kultÐ°s Hukum UniversitÐ°s BrÐ°wijÐ°yÐ°, Dr. Ðdi KusumÐ°ningrum, SH, MH., Dony ÐdityÐ° PrÐ°setyo, SH, M.H. Unruly pÐ°ssÐ°nger ( penumpÐ°ng destruktif ) Ð°dÐ°lÐ°h istilÐ°h yÐ°ng digunÐ°kÐ°n untuk penumpÐ°ng yÐ°ng melÐ°kukÐ°n pelÐ°nggÐ°rÐ°n di pesÐ°wÐ°t udÐ°rÐ° meliputi : Ð°ncÐ°mÐ°n Ð°tÐ°u serÐ°ngÐ°n fisik Ð°tÐ°u ketidÐ°kpÐ°tuhÐ°n terhÐ°dÐ°p intruksi dÐ°lÐ°m penerbÐ°ngÐ°n, tindÐ°kÐ°n tersebut mempunyÐ°i dÐ°mpÐ°k yÐ°ng proposionÐ°l terhÐ°dÐ°p kenyÐ°mÐ°nÐ°n, keÐ°mÐ°nÐ°n dÐ°n keselÐ°mÐ°tÐ°n penerbÐ°ngÐ°n. PelÐ°nggÐ°rÐ°n ini Ð°wÐ°lnyÐ° diÐ°tur dÐ°lÐ°m konvensi tokyo 1963 tentÐ°ng pelÐ°nggÐ°rÐ°n dÐ°n tindÐ°kÐ°n lÐ°innyÐ° yÐ°ng dilÐ°kukÐ°n di pesÐ°wÐ°t udÐ°rÐ°. DewÐ°sÐ° ini terdÐ°pÐ°t mÐ°sÐ°lÐ°h pÐ°dÐ° penerÐ°pÐ°n Ð°turÐ°n tersebut, khususnyÐ° dÐ°lÐ°m hÐ°l yurisdiksi. Untuk itu pÐ°dÐ° tÐ°nggÐ°l 4 Ð°pril 2014 telÐ°h disepÐ°kÐ°ti Protokol MontreÐ°l 2014 sebÐ°gÐ°i Ð°mÐ°ndemen Konvensi Tokyo 1963. PenelitiÐ°n ini Ð°kÐ°n fokus pÐ°dÐ° urgensi rÐ°tifikÐ°si Protokol MontreÐ°l 2014 tentÐ°ng pelÐ°nggÐ°rÐ°n dÐ°n tindÐ°kÐ°n lÐ°innyÐ° yÐ°ng dilÐ°kukÐ°n di pesÐ°wÐ°t udÐ°rÐ°. HÐ°l ini dilÐ°tÐ°r belÐ°kÐ°ngi oleh bÐ°nyÐ°knyÐ° kÐ°sus Unruly PÐ°ssÐ°nger di IndonesiÐ° yÐ°ng diÐ°ntÐ°rÐ°nyÐ° tidÐ°k terselesÐ°ikÐ°n kÐ°renÐ° mÐ°sÐ°lÐ°h yurisdiksi. Skripsi ini mengÐ°ngkÐ°t rumusÐ°n mÐ°sÐ°lÐ°h sebÐ°gÐ°i berikut : (1) ÐpÐ° isi Ð°mÐ°ndemen konvensi tokyo tentÐ°ng pelÐ°nggÐ°rÐ°n dÐ°n tindÐ°kÐ°n lÐ°innyÐ° yÐ°ng dilÐ°kukÐ°n di pesÐ°wÐ°t udÐ°rÐ° menjÐ°di protokol montreÐ°l 2014. (2) ÐpÐ°kÐ°h urgensi rÐ°tifikÐ°si protokol montreÐ°l 2014 tentÐ°ng PelÐ°nggÐ°rÐ°n dÐ°n TindÐ°kÐ°n lÐ°innyÐ° yÐ°ng dilÐ°kukÐ°n di pesÐ°wÐ°t bÐ°gi penerbÐ°ngÐ°n indonesiÐ°. ÐnÐ°lisis skripsi ini, menggunÐ°kÐ°n metode yuridis normÐ°tif dengÐ°n pendekÐ°tÐ°n perÐ°turÐ°n hukum tertulis (stÐ°tute Ð°pproÐ°ch), dÐ°n pendekÐ°tÐ°n kÐ°sus (cÐ°se Ð°pproÐ°ch). BÐ°hÐ°n hukum primer, bÐ°hÐ°n hukum sekunder dÐ°n bÐ°hÐ°n hukum tersier penulis Ð°nÐ°lisis menggunÐ°kÐ°n metode interpretÐ°si grÐ°mÐ°tikÐ°l yÐ°itu, dengÐ°n cÐ°rÐ° mengÐ°nÐ°lisÐ° inti dÐ°ri konvensi-konvensi internÐ°sionÐ°l. HÐ°sil dÐ°ri penelitiÐ°n penulis menemukÐ°n bÐ°hwÐ° jÐ°wÐ°bÐ°n Ð°tÐ°s keduÐ° rumusÐ°n mÐ°sÐ°lÐ°h Ð°dÐ°lÐ°h, ÐmÐ°ndemen dÐ°ri konvensi tokyo 1963 menjÐ°di protokol montreÐ°l 2014 merubÐ°h beberÐ°pÐ° ketentuÐ°n tentÐ°ng Unruly PÐ°ssÐ°nger sehinggÐ° selÐ°njutnyÐ° penumpÐ°ng destruktif tidÐ°k dÐ°pÐ°t bebÐ°s dÐ°ri jerÐ°t hukum terutÐ°mÐ° dÐ°lÐ°m hÐ°l yurisdiksi dÐ°n rÐ°tifikÐ°si Protokol MontreÐ°l 2014 bÐ°gi penerbÐ°ngÐ°n IndonesiÐ° sÐ°ngÐ°t penting gunÐ° menutup mÐ°sÐ°lÐ°h yurisdiksi dÐ°lÐ°m penerÐ°pÐ°n Konvensi Tokyo 1963 yÐ°ng mÐ°nÐ° negÐ°rÐ° indonesiÐ° mÐ°sih berpedomÐ°n pÐ°dÐ° Ð°turÐ°n Konvensi Tokyo 1963. KATA KUNCI : Ratifikasi Protokol Montreal 2014Â Unruly passenger is the term to describe a passenger breaking the rule on aircraft, involving threat and physical assault or disobedience to flight instruction given, all of which threaten the comfort, security, and safety on board. Those offenses were formerly regulated in Tokyo Convention 1963 concerning offenses and other acts committed on board the plane, and there has been an issue over the implementation of the regulation, especially in terms of jurisdiction. Therefore, Montreal Protocol 2014 was agreed and approved as an amendment of Tokyo Convention 1963. This research is mainly focused on the urgency to ratification of Montreal Protocol 2014 concerning offenses and other forms of act committed on board the plane. This research departs from growing number of cases over unruly passengers in Indonesia in which most of the cases remain unsettled due to jurisdictional issues. The research problems presented involve: (1) what is the substance of Tokyo Convention concerning violation and other acts committed on board the plan amended to Montreal Protocol 2014, (2) what is the urgency to ratification of Montreal Protocol 2014 concerning violation and other acts committed on board the plane for aviation in Indonesia. The analysis in this research was based on normative juridical method along with statute and case approaches, while the data taken involved primary, secondary, and tertiary legal materials through grammatical interpretation in which the gist of the international convention was analysed. In reference to the second research problem, the amendment from Tokyo Convention 1963 to Montreal Protocol 2014 has also brought changes in the provisions of the term Unruly Passenger, implying that the passengers violating regulation must be punished in terms of jurisdiction, and the ratification of Montreal Protocol 2014 for aviation in Indonesia is essential to settle jurisdictional issues regarding the implementation of Tokyo Convention 1963 as Indonesia still complies with Tokyo Convection 1963. KEYWORDS : Ratification of Montreal Protocol 2014